Culturally adapted pulmonary rehabilitation for adults living with post-tuberculosis lung disease in Kyrgyzstan: protocol for a randomised controlled trial with blinded outcome measures. Issue 2 (21st February 2022) - Akylbekov, Azamat; Orme, Mark W; Jones, Amy V; Mademilov, Maamed; Muratbekova, Aibermet; Aidaralieva, Shoira; Mirzalieva, Gulzada; Oleinik, Alena; Magdieva, Kamila; Taalaibekova, Aijan; Rysbek kyzy, Aidai; Yusuf, Zainab K; et al.
Abstract : Introduction: Pulmonary rehabilitation (PR) is a programme of individually prescribed physical exercise, education and self-management activities. PR is recommended in international guidelines for managing chronic obstructive pulmonary disease (COPD) and other chronic respiratory diseases. PR is still under-recognised in tuberculosis (TB) guidelines and PR is not available in many low and middle-income countries and for people with post-TB lung disease (PTBLD). The main aims of the study are to adapt and define a culturally appropriate PR programme in Kyrgyzstan for people living with PTBLD and to test, in a fully powered randomised controlled trial (RCT), the effectiveness of PR in improving exercise capacity for people living with PTBLD. Methods and analysis: The study will be divided into three stages: stage 1: focus group discussions with patients living with PTBLD and interviews with PR referrers will be conducted to explore initial perceptions and inform the cultural adaptation, structure and content of PR. Stage 2a: a single-blind RCT evaluating the effectiveness of a culturally adapted 6-week PR programme on maximal exercise capacity, assessed by the incremental shuttle walking test, before and after PR. Participants will be additionally followed-up 12 weeks postbaseline. Additional outcomes will include health-related quality of life, respiratory symptoms, psychological well-being and physical function. Stage 2b: participants' experience of PR will be collected through interviews and using a log book and a patient evaluation form. Staff delivering PR will be interviewed to explore their experience of delivering the intervention and refining the delivery for future implementation. Ethics and dissemination: The study was approved 22/07/2019 by Ethics Committee National Center for Cardiology and Internal Medicine (reference number 17) and by University of Leicester ethics committee (reference number 22293). Study results will be disseminated through appropriate peer-reviewed journals, national and international respiratory/physiotherapy conferences, social media, and through patient and public involvement events in Kyrgyzstan and in the UK. Trial registration number: ISRCTN11122503 .